2005
DOI: 10.1007/bf03403693
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Risk Factors for Poor Diet Quality Among Children in Nova Scotia

Abstract: Objective: Public health policies promote healthy nutrition but evaluations of children's adherence to dietary recommendations and studies of risk factors of poor nutrition are scarce, despite the importance of diet for the temporal increase in the prevalence of childhood obesity. Here we examine dietary intake and risk factors for poor diet quality among children in Nova Scotia to provide direction for health policies and prevention initiatives. Methods: In 2003, we surveyed 5,200 grade five students from 282… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
54
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 34 publications
15
54
1
1
Order By: Relevance
“…When specific food categories were analyzed, the highest amounts of other foods, fried foods, and pizza were consumed between places or at a restaurant/fast food outlet, alone or with friends, and self‐prepared or prepared by others from food purchased at a restaurant or fast food outlet. These data are not all that surprising particularly with the recent food intake literature among children and adolescents 15–18 . However, given that the lunch meal is generally consumed at school, it was discouraging to note that ∼11% of the foods consumed were eaten between places or at a restaurant/fast food outlet.…”
Section: Discussionmentioning
confidence: 86%
“…When specific food categories were analyzed, the highest amounts of other foods, fried foods, and pizza were consumed between places or at a restaurant/fast food outlet, alone or with friends, and self‐prepared or prepared by others from food purchased at a restaurant or fast food outlet. These data are not all that surprising particularly with the recent food intake literature among children and adolescents 15–18 . However, given that the lunch meal is generally consumed at school, it was discouraging to note that ∼11% of the foods consumed were eaten between places or at a restaurant/fast food outlet.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Veugelers et al [8] reported that skipping breakfast was associated with an approximately 18 % increase in the risk of a poor diet in children. On this basis, we assessed the mediation effect of eating breakfast on the association between socioeconomic indicators and children’s dietary quality.…”
Section: Discussionmentioning
confidence: 98%
“…The socioeconomic benefits of educational attainment carry forward to future generations as children from socioeconomically advantaged backgrounds are more likely to succeed in school. Moreover, as increased levels of educational attainment and income facilitate increased understanding of nutrition messages and access to healthy food, 24,32,33 children from socioeconomically advantaged families are more likely to consume healthy diets. Increased diet quality among these children will provide further benefit to their academic performance and, in terms of health, contribute to healthy child development, which influences health throughout the life course.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the administration of the surveys and measurement of heights and weights took less than 45 minutes to complete. Further details on the conduct of the CLASS are provided elsewhere 10,24,25 …”
Section: Methodsmentioning
confidence: 99%